Endovascular versus neurosurgical aneurysm treatment: study protocol for the development and validation of a clinical prediction tool for individualised decision making - Hester F Lingsma; Diederik W J Dippel; David van Klaveren; Bob Roozenbeek; Mathieu van der Jagt; Ruben Dammers; Pieter-Jan van Doormaal; Jordi de Winkel; Simone A Dijkland (BMJ Open)
Introduction Treatment decisions for aneurysmal subarachnoid haemorrhage patients should be supported by individualised predictions of the effects of aneurysm treatment. We present a study protocol and analysis plan for the development and external validation of models to predict benefit of neurosurgical versus endovascular aneurysm treatment on functional outcome and durability of treatment.Methods and analysis We will use data from the International Subarachnoid Aneurysm Trial for model development. The outcomes are functional outcome, measured with modified Rankin Scale at 12 months, and any retreatment or rebleed of the target aneurysm during follow-up. We will develop an ordinal logistic regression model and Cox regression model, considering age, World Federation of Neurological Surgeons grade, Fisher grade, vasospasm at presentation, aneurysm lumen size, aneurysm neck size, aneurysm location and time-to-aneurysm-treatment as predictors. We will test for interactions with treatment and with baseline risk and derive individualised predicted probabilities of treatment benefit. A benefit of ≥5% will be considered clinically relevant. Discriminative performance of the outcome predictions will be assessed with the c-statistic. Calibration will be assessed with calibration plots. Discriminative performance of the benefit predictions will be assessed with the c-for benefit. We will assess internal validity with bootstrapping and external validity with leave-one-out internal-external cross-validation.Ethics and dissemination The medical ethical research committee of the Erasmus MC University Medical Center Rotterdam approved the study protocol under the exemption category and waived the need for written informed consent (MEC-2020-0810). We will disseminate our results through an open-access peer-reviewed scientific publication and with a web-based clinical prediction tool.